Analisis Penerimaan Mahasiswa Terhadap Articulate Storyline Menggunakan Model TAM - Lathifah, Afra; Isni Kurnia, Ulfa; Hertati, Elvani; Yudha Pratama, Rendy (Jurnal Pendidikan Teknologi Informasi (J-Diteksi), 2024)
The use of technology in the educational context continues to grow in line with advances in information technology. Articulate Storyline has emerged as a widely used learning media development tool. This phenomenon provides an opportunity to further examine how students accept the use of Articulate Storyline. By using the TAM (Theory of Acceptance Model), the research results show that Articulate Storyline is assessed positively because of its ease of use and benefits by the majority of students. However, some students still expressed uncertainty or were neutral regarding the intention to use Articulate Storyline consistently. Factors such as individual characteristics, previous technology experience, and learning environment can also be taken into consideration in understanding student acceptance of learning technology.